2013
DOI: 10.1590/1678-775720130114
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength to root dentin and fluid filtration test of AH Plus/gutta-percha, EndoREZ and RealSeal systems

Abstract: 6XEPLWWHG -DQXDU\ 0RGL¿FDWLRQ 0D\ $FFHSWHG -XQHO bjectives: To investigate the bond strength and seal ability produced by AH Plus/guttapercha, EndoREZ and RealSeal systems to root canal dentin. Material and Methods: Sixty extracted single-root human teeth, instrumented manually to size 40, were divided into three groups (n=20) according to the sealer used; G1: AH Plus, G2: EndoREZ, and * 5HDO6HDO VHDOHUV $IWHU ¿OOLQJ XVLQJ WKH ODWHUDO FRQGHQVDWLRQ WHFKQLTXH HDFK VHDOHU group was randomly divided into two subgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
3
6
0
3
Order By: Relevance
“…A probable explanation could be the high c-factor (ratio of bonded to unbounded resin surfaces) seen in root canals, which concentrates high polymerization stresses between resin-based materials and the canal walls; these stresses may exceed the bond strength of adhesives to dentin, resulting in gap formation along the surfaces [20] . This finding confirmed those of previous studies [9][10][11]21] which showed that EndoREZ ® has low push-out bond strength. The push-out bond strength of G4 and G5 decreased further at 3 months compared to 2 weeks after obturation and remained the lowest in bond strength among all groups.…”
Section: Discussionsupporting
confidence: 93%
“…A probable explanation could be the high c-factor (ratio of bonded to unbounded resin surfaces) seen in root canals, which concentrates high polymerization stresses between resin-based materials and the canal walls; these stresses may exceed the bond strength of adhesives to dentin, resulting in gap formation along the surfaces [20] . This finding confirmed those of previous studies [9][10][11]21] which showed that EndoREZ ® has low push-out bond strength. The push-out bond strength of G4 and G5 decreased further at 3 months compared to 2 weeks after obturation and remained the lowest in bond strength among all groups.…”
Section: Discussionsupporting
confidence: 93%
“…5,6,7,8,9 In the present study, the bond strength performance of single matched-taper gutta-percha cone techniques of reciprocating NiTi systems with different sealers was evaluated and compared with that of the lateral compaction technique. The results demonstrated that the bond strength of the filling material to the root canal is dependent on both the filling technique and the sealer.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,7,8,9 Methacrylate resin-self-adhesive sealers such as Epiphany SE (Pentron Clinical Technologies, Wallingford, USA) and its successor RealSeal SE (Sybron Endo, Glendora, USA) were developed to improve the root filling bonding to the root dentin. 10 However, controversial results have been reported with respect to the adhesiveness of these sealers.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Hand instrumentation technique was used to prepare the root canals because it is still widely used throughout the world (18) . Smear layer was removed with 1 ml of 17% EDTA used for 1 min which increase the penetration of the sealer into the dentinal tubules, and its mechanical interlocking to the canal walls (6) .…”
Section: Discussionmentioning
confidence: 99%